Public Employee Discipline - Muhammad Wahid; Sirajuddin Saleh; Isgunandar (Journal of Public Policy and Local Government (JPPLG), 2024)
The achievement of the goals, vision and mission of an agency or institution cannot be realized without the role and cooperation of parties in it. This research aims to analyze and document Employee Discipline in the office of the Food Security Office of South Sulawesi Province. This research is a qualitative research with data collection techniques using observation, interview and documentation methods with informant subjects, one of the leaders and four people who are also staff at the Office of the Food Security Office of South Sulawesi Province. The results of this research show that employee discipline at the Office of the Food Security Office of South Sulawesi Province is still lacking. This can be seen from the indicators of discipline, namely presence, responsibility, attitude, and norms. Where employees are present less in accordance with established regulations and observations proven through attendance list recaps, the implementation of responsibilities that are included in the category of very good, very good attitudes, and compliance with regulations that are still not good. The results of this research are still not as expected based on discipline indicators. This study presents new information by linking detailed theories and research loci different from previous research on employee discipline so that it can be used as evaluation material for research loci to improve employee discipline